HPV vaccines: Global perspectives. Issue 6 (3rd June 2017) - Gupta, Gaurav; Glueck, Reinhard; Patel, Pankaj R.
ABSTRACT: The discovery of HPV as the etiological factor for HPV-associated malignancies and disease has opened up several opportunities for prevention and therapy. Current commercially available HPV vaccines (Gardasil, Gardasil 9, and Cervarix) are prophylactic in nature and derived from adjuvanted L1-based virus-like particles of HPV. Globally, through several clinical trials, they were found to be very safe and efficacious. Certain limitations such as cost-effectiveness, low coverage against all HPV types and a 3-dose schedule make these vaccines difficult to use worldwide. Approaches to address these issues involve alternate expression systems using L1 or alternate antigen (L2) as well as optimizing doses and broadening protection to provide cheap and cross-protective vaccines. Additionally, promising preclinical immunogenicity results from our own studies using alternative hosts such as Pichia and an antigen delivery system-based measles vector have potential for development as next generation HPV prophylactic vaccines. Several other therapeutic approaches are also ongoing.